Mechanical Properties of Chemically Treated Luffa Aegyptiaca Fiber Reinforced Epoxy Matrix Composites - and K.Vigne, C.Srinivasan* , S.Sathish (International Journal of Scientific Research and Management (IJSRM), 2014)
In recent year natural fiber composite material place a major role in aerospace and automobileindustries. Natural fibers such as flax, hemp, kenaf and jute are derived from renewable resources andconsequently are perceived as environmentally friendly materials. Natural fibers are reported to haveadvantages of lower cost and better stiffness per unit weight compared to other materials. In this projectthe natural fiber is Luffa aegyptiaca Fibers are alkaline treated and dried out in sunlight. The various wt% of discontinued fibers are laminated with epoxy resin and the laminates are prepared by hand layupprocess. The Mechanical properties of natural fiber composites such as tensile, compressive, impact andflexural strength has founded and compared. Then, SiO2 nano particles synthesized in sol-gel method andthey are induced with epoxy to improve the certain mechanical property of the composite material. Mostmajor automobile manufacturers are currently using natural fiber Composites for different parts insideand outside cars and buses. Such as dash board ceilings, seat filling, door trim, door cladding. Consumerand industrial uses include flowerpots and lawn furniture.